Kajian Tahlili Amal Al-Syaitan Perspektif Al-Qur’an Surah Al-Qasah Ayat 15 - Arif Rahman; Yan Abdillah Amir (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2023)
This study aims to reveal the ‘amal al-syaita>n (deeds of the devil) in QS. al-Qasas/28: 15. This type of research is qualitative and takes the form of literature research. The approach used is the interpretation approach. The data used are primary data sourced from the Koran and books of interpretation and secondary data, including related works and other references that can support research, then processed and analyzed using the Tahlili method. The results of the research show that the essence of ‘amal al-syaita>n (deeds of the devil) in QS. al-Qasas/28: 15 are all forms of action, whether committed by humans or jinn, where these actions contain hatred and hostility and are considered disgraceful, cause evil, iniquity, and disbelief so as to keep the perpetrator away from the truth and mercy of Allah swt. Form of ‘amal al-syaita>n (deeds of the devil) in QS. al-Qasas/28: 15, namely emotions, haste in making decisions, and murder.